MORPHOLOGICAL ANALYSIS AND COMPOSITION OF NICKEL LAYER USING PULSE CURRENT ELECTRODEPOSITION: ANALISIS MORFOLOGI DAN KOMPOSISI LAPISAN NIKEL MENGGUNAKAN ELEKTRODEPOSISI RAPAT ARUS PULSA - Bayyinah; Esmar Budi; Teguh Budi Prayitno (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
In this study, Nickel layers were deposited on a Tungsten Carbide (WC) substrate using pulse current densities of 0.35 and 0.4 mA/mm2. The Nickel deposition was performed by electrodeposition for 30 minutes at a temperature of 40°C with a stirring rate of 600 rpm. Based on the SEM characterization results, the Nickel layer at a magnification of 1000x showed that at a current density of 0.35 mA/mm2, the particle distribution was uniform, with no cracks or agglomeration on the substrate surface, and the particles were larger and more homogeneous. In contrast, at a current density of 0.4 mA/mm2, the particle distribution was less uniform, there were no cracks or agglomeration on the substrate surface, and the particles appeared smaller and homogeneous, resulting in a smoother Nickel layer surface. The EDS scanning results indicated the successful formation of the Nickel layer, with the presence of Ni metal content, which increased with the current density from 0.35 to 0.4 mA/mm2.